Search
Ask a question
0

How do you factor x^2(x+2)-(x+2) ?

Factor in quadratic form.

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Tamara J. | Math Tutoring - Algebra and Calculus (all levels)Math Tutoring - Algebra and Calculus (al...
4.9 4.9 (51 lesson ratings) (51)
0

     x2(x + 2) - (x + 2)

Notice that there is a greatest common factor (gcf) that you can factor out of the entire equation, that being: x + 2

    x2(x + 2) - 1(x + 2)    ==>    (x + 2) ( x2(1) - 1(1) )    ==>    (x + 2)(x2 - 1) 

Thus,     x2(x + 2) - (x + 2)  =  (x2 - 1)(x + 2) 

Robert J. | Certified High School AP Calculus and Physics TeacherCertified High School AP Calculus and Ph...
4.6 4.6 (13 lesson ratings) (13)
0

x2(x+2)-(x+2)

= (x+2)(x2-1), factor out x+2 first

= (x+2)(x+1)(x-1), since x2-1 = (x+1)(x-1)